Changes in the incidence of cervical tumours by disease stage in a cytology-based screening programme. (June 2020) - Bucchi, Lauro; Mancini, Silvia; Baldacchini, Flavia; Giuliani, Orietta; Ravaioli, Alessandra; Vattiato, Rosa; Falcini, Fabio; Giorgi Rossi, Paolo; Campari, Cinzia; Canuti, Debora; Di Felice, Enza; de Bianchi, Priscilla Sassoli; et al.
Objectives: To report changes in incidence of cervical tumours by disease stage, following the introduction of an organized cytology-based screening programme. Methods: An intention-to-screen study of a cytology-based screening programme targeting 1, 219, 000 women aged 25–64 in northern Italy was carried out. Based on the previously reported trend in total incidence of cervical cancer, the study period 1995–2014 was divided into 1995–1996 (pre-screening, or reference, years), 1997–1998 (screening implementation phase), 1999–2006 (transition phase, when incidence decreased), and 2007–2014 (steady-state phase, when incidence stabilized again). Tumour stage was categorized as preinvasive (cervical intraepithelial neoplasia grade 3 (CIN3) and adenocarcinoma in situ), early (pT1a), advanced (pT1b or greater, ypT), and unknown (pT1 not otherwise specified, pTx, missing information). Average annual incidence rates observed in each phase were compared with the expected (reference) rates, using the incidence rate ratio, calculated with a Poisson regression model. Results: In the steady-state phase, incidence rate ratios were: CIN3, 1.55 (95% confidence interval, 1.41–1.70); early-stage squamous carcinoma, 0.49 (0.36–0.67); advanced-stage squamous carcinoma, 0.44 (0.33–0.57); unknown-stage squamous carcinoma, 0.69 (0.48–0.99); adenocarcinoma in situ, 1.44 (0.72–2.88); early-stage adenocarcinoma, 2.65 (0.82–8.53); advanced-stage adenocarcinoma, 1.03 (0.56–1.91); and unknown-stage adenocarcinoma, 0.46 (0.23–0.92). Conclusions: After stabilization, changes in incidence by tumour stage included a 55% increase for CIN3 and a 50–55% decrease both for early- and advanced-stage squamous carcinoma, but no significant changes for glandular tumours. These data will serve to quantify the incremental impact of the implementation of human papillomavirus-based screening, introduced in 2015.